6p+-3(4p+3)+4(6p+1)=43

Simple and best practice solution for 6p+-3(4p+3)+4(6p+1)=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p+-3(4p+3)+4(6p+1)=43 equation:


Simplifying
6p + -3(4p + 3) + 4(6p + 1) = 43

Reorder the terms:
6p + -3(3 + 4p) + 4(6p + 1) = 43
6p + (3 * -3 + 4p * -3) + 4(6p + 1) = 43
6p + (-9 + -12p) + 4(6p + 1) = 43

Reorder the terms:
6p + -9 + -12p + 4(1 + 6p) = 43
6p + -9 + -12p + (1 * 4 + 6p * 4) = 43
6p + -9 + -12p + (4 + 24p) = 43

Reorder the terms:
-9 + 4 + 6p + -12p + 24p = 43

Combine like terms: -9 + 4 = -5
-5 + 6p + -12p + 24p = 43

Combine like terms: 6p + -12p = -6p
-5 + -6p + 24p = 43

Combine like terms: -6p + 24p = 18p
-5 + 18p = 43

Solving
-5 + 18p = 43

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 18p = 43 + 5

Combine like terms: -5 + 5 = 0
0 + 18p = 43 + 5
18p = 43 + 5

Combine like terms: 43 + 5 = 48
18p = 48

Divide each side by '18'.
p = 2.666666667

Simplifying
p = 2.666666667

See similar equations:

| 5(m-2)=-(6m-1) | | x(x-9)(x+3)=0 | | Z-6.8=7.56 | | 0=6x+x^2-31 | | 1620x-350=680x+470 | | 1/3p-p=12 | | (8x+3)(5x+8)=180 | | 3x+9(3x+1)=9x-6 | | 6(4x+3)=138 | | 5x+9i=10-3yi | | 2x+9+9x-8=8x+19 | | 15x-3(6+5x)=-18 | | x*x=16+(x+-4)(x+2) | | 8+6y=7y | | 2x+6=-6-2 | | -4(v+7)=-(1+7v) | | 14.3=-1.4-3d | | x*x=16+(x-4)*(x+4) | | P/g=10 | | 9x-5-6x-2=6x-1 | | -10-9z+10z=-12 | | 5g+2=10-3g-8 | | -5r+5=-6r+2 | | (3x-1)(6x+9)=0 | | (x-4)*(x+4)=486 | | 3.50t+5.50+6t=51 | | d+6=10-3d | | 1-7n-1=-8n | | (x-4)*(x-4)=486 | | 60+60+x-20=360 | | 9x-5-6x-2=6x-7 | | -4n+6n=6n-12 |

Equations solver categories